The Barrier and Driver Factors of Building Information Modelling (BIM) Adoption in Indonesia: A Preliminary Survey - Faizal Restu Utomo; Mohammad Arif Rohman (IPTEK Journal of Proceedings Series, 2019)
Building information modeling (BIM) changes institutions, businesses, business models, education, workplaces and careers. For an asset owner the implementation of BIM should seen as a business change program that can potentially impact their ‘value proposition’. BIM can enable strategic business outcomes. BIM is useful for geometric modelling of a building's performance and it can assist in the management of construction projects. The construction industry in the world has recognized the benefits of BIM, therefore many large projects in developed countries have used BIM. In Indonesia, lately BIM has received more attention from construction industry players, even the Indonesian government through the public works agency issued guidelines for BIM adoption in 2018 with reference to developed country references such as Singapore. Many benefits can be obtained from the implementation of BIM, but the level of BIM adoption in Indonesia is still low. Thus, it warrants a study such as the present to determine what are the actual barriers that hamper its implementation and what are the driving factors that could enhance its pace of implementation in the Indonesian construction industry. This paper is an initial stage of the research to determine the barriers and driving factors of building information modelling (BIM) adoption in Indonesia. Following the variable identification from the literature, a preliminary survey involving eleven experts were conducted to verify several variables that have been identified from the literature to be used for the questionnaire survey. According to the experts’ opinion, it was found that 16 variables were considered relevant to measure the barriers of BIM adoption in Indonesia and 18 variables were considered relevant to measure the driving factors of BIM Adoption in Indonesia. The three most relevant barriers BIM adoption in Indonesia attributes were also determined according to the experts’ opinion, that are (1) Lack of BIM expert; (2) Lack of understanding about BIM and its benefits; (3) Resistance to change. The three most relevant drivers BIM adoption in Indonesia attributes were also determined according to the experts’ opinion, that are (1) Willingness/intention; (2) Technological factors; (3) Organizational culture